The Influence of Workload and Compensation on Employee Performance at J&T Express Couriers in the North Surabaya Region - Fachmi Nursyamsi; Sulastri Irbayuni (Universitas KH. Abdul Chalim Mojokerto, 2025)
To support and advance a company, everything depends on existing human resources. Because human resources have an important role in a company because human resources are what determine the success of a company in the long term. However, in reality, there are many challenges that employees must face in supporting the successful performance of a company. This research aims to determine the effect of workload and compensation on employee performance. The method used is a quantitative method with a population of 40 J&T Express employees in the North Surabaya Region and the sampling technique uses saturated sampling, namely the sample takes the entire population of 40 courier employees. Data was obtained through a questionnaire compiled based on indicators for each research variable and then analyzed using SmartPLS software. The results of the research show that a high workload can reduce employee performance and providing good compensation can improve employee performance for J&T Express couriers in the North Surabaya Region.